Function of metals and supports on the hydrodeoxygenation of phenolic compounds - Deepa, Ayillath K.; Dhepe, Paresh L. (ChemPlusChem, 2014)
Hydrodeoxygenation (HDO) is an important process for removing oxygen from lignin-derived phenolic monomers to obtain chemicals that can be used as fuel or fuel additives. A systematic study is performed to check the effects of supports (acidic, neutral, basic) and noble metals (Pd, Pt, Ru) on the HDO of phenol, guaiacol, and eugenol. Evaluation of the combinations of metals and supports under the similar reaction conditions shows that the metals supported on a highly acidic support (SiO2-Al2O3) yield complete hydrogenation products with the possibility of C[BOND]O bond cleavage to achieve a real HDO activity, whereas on a mildly acidic support (gamma-Al2O3), a complicated product distribution is achieved, and neutral (C) and basic (HT) supports give restricted hydrogenation activity but yield the products with very high selectivity. On the basis of the results, reaction pathways are suggested and deliberated. The catalysts show reproducible activity in recycle runs. The catalysts are characterized by various techniques (XRD, TEM, TPD, ICP-OES) to establish the catalyst activityproperty relationship.

Solid acid catalyzed depolymerization of lignin into value added aromatic monomers - Deepa, Ayillath K.; Dhepe, Paresh Laxmikant (RSC Advances, 2014)
Depolymerization of lignin to produce value-added aromatic monomers has attracted a lot of attention since these monomers can potentially be used as fuel additives (octane enhancers) and in turn can improve the prospects of cellulosic ethanol technology to become economically feasible. Here we show that solid acid catalysts could efficiently convert lignin into value added aromatic monomers with 60% yields and ca. 95% mass balance when depolymerization reactions were carried out at 250 degrees C for 30-120 minutes. We found that the reaction parameters have a remarkable effect on improving the yields.

Value addition to lignocellulosics and biomass-derived sugars: an insight into solid acid-based catalytic methods - Bhaumik, Prasenjit; Deepa, Ayillath K.; Kane, Tanushree; Dhepe, Paresh Laxmikant (Journal of Chemical Sciences, 2014)
For the synthesis of important platform chemicals such as sugars (xylose and arabinose) and furans (furfural and 5-hydroxymethylfurfural (HMF)) from carbohydrates (hemicellulose and fructose) solid acid catalysts are employed. Similarly, over solid acid catalysts, conversion of lignin into aromatic monomers is performed. It is observed that in the dehydration of fructose, because of higher hydrothermal stability, silicoaluminophosphate (SAPO) catalysts give better activity (78% HMF yield) compared with other solid acid catalysts (<63% HMF yield) at 175 degrees C. Particularly, SAPO-44 catalyst can be reused at least 5 times with marginal decrease in the activity. Zeolite, BUSY (Si/Al = 15) is active in the conversion of isolated (pure) hemicellulose to produce 41% C-5 sugars in water. The catalyst is also active in the selective conversion of hemicellulose from bagasse to yield 59% C-5 sugars. It is possible to obtain high yields of furfural (54%) directly from bagasse if instead of water, Water+toluene solvent system is used. Depolymerization of lignin using HUSY catalyst produced aromatic monomers with 60% yield at 250 degrees C. A detailed catalyst characterization study is performed to understand the correlation between catalyst activity and morphology. To understand the effect of impurities present in the substrate over solid acid catalysts, metal-exchange study is carried out.
Keywords: aromatic monomers; Biomass; furans; Hemicellulose; lignin; solid acid catalyst

Lignin depolymerization into aromatic monomers over solid acid catalysts - Deepa, Ayillath K.; Dhepe, Paresh Laxmikant (ACS Catalysis, 2015)
It is imperative to develop an efficient and environmentally benign pathway to valorize profusely available lignin, a component of nonedible lignocellulosic materials, into value-added aromatic monomers, which can be used as fuel additives and platform chemicals. To convert lignin, earlier studies used mineral bases (NaOH, CsOH) or supported metal catalysts (Pt, Ru, Pd, Ni on C, SiO2, Al2O3, etc.) under a hydrogen atmosphere, but these methods face several drawbacks such as corrosion, difficulty in catalyst recovery, sintering of metals, loss of activity, etc. Here we show that under an inert atmosphere various solid acid catalysts can efficiently convert six different types of lignins into value-added aromatic monomers. In particular, the SiO2Al2O3 catalyst gave exceptionally high yields of ca. 60% for organic solvent soluble extracted products with 95 +/- 10% mass balance in the depolymerization of dealkaline lignin, bagasse lignin, and ORG and EORG lignins at 250 degrees C within 30 min. GC, GC-MS, HPLC, LC-MS, and GPC analysis of organic solvent soluble extracted products confirmed the formation of aromatic monomers with ca. 90% selectivity. In the products, confirmation of retention of aromatic nature as present in lignin and the appearance of several functional groups has been carried out by FT-IR and H-1 and C-13 NMR studies. Further, isolation of major products by column chromatography was carried out to obtain aromatic monomers in pure form and their characterization by NMR is presented. A detailed characterization of six different types of lignins obtained from various sources helped in substantiating the catalytic results obtained in these reactions. A meticulous study on fresh and spent catalysts revealed that the amorphous catalysts are preferred to obtain reproducible catalytic results.
Keywords: aromatic monomers; Biomass; column chromatography; depolymerization; lignin; solid acid catalysts